2017
DOI: 10.1371/journal.pone.0179375
|View full text |Cite
|
Sign up to set email alerts
|

Formation and spreading of TDP-43 aggregates in cultured neuronal and glial cells demonstrated by time-lapse imaging

Abstract: TAR DNA-binding protein 43 (TDP-43) is a main constituent of cytoplasmic aggregates in neuronal and glial cells in cases of amyotrophic lateral sclerosis and frontotemporal lobar degeneration. We have previously demonstrated that adenovirus-transduced artificial TDP-43 cytoplasmic aggregates formation is enhanced by proteasome inhibition in vitro and in vivo. However, the relationship between cytoplasmic aggregate formation and cell death remains unclear. In the present study, rat neural stem cell lines stably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(62 citation statements)
references
References 52 publications
4
58
0
Order By: Relevance
“…The TDP-43 fragments were designed based on the borders of TDP-43 LCD segments determined by Schmidt and colleagues [ 28 ]. Like others [ 34 , 55 ], we showed that full-length wild-type TDP-43 only rarely forms aggregates when expressed in cultured cells. Moreover, in accordance with the literature [ 34 ], our expressed dNLS readily aggregated in the cytoplasm, forming numerous small aggregates, in about a quarter of transfected cells.…”
Section: Discussionsupporting
confidence: 86%
“…The TDP-43 fragments were designed based on the borders of TDP-43 LCD segments determined by Schmidt and colleagues [ 28 ]. Like others [ 34 , 55 ], we showed that full-length wild-type TDP-43 only rarely forms aggregates when expressed in cultured cells. Moreover, in accordance with the literature [ 34 ], our expressed dNLS readily aggregated in the cytoplasm, forming numerous small aggregates, in about a quarter of transfected cells.…”
Section: Discussionsupporting
confidence: 86%
“…Again, in exogenous TDP-43-expressing cells, UPS inhibition induces TDP-43 aggregates containing phosphorylated TDP-43 [190]. These aggregates remain insoluble in culture media, consisting of sarkosyl-insoluble granular materials, and remarkably, they are released into neighboring neuronal cells, suggesting a cell-to-cell propagation [190].…”
Section: Cell-clearing Systems and Prion-like Protein Propagationmentioning
confidence: 96%
“…The ubiquitinproteasome system is disrupted by ALS-linked mutations in Ubiquilin-2 (UBQLN2), and is important for degrading full-length TDP-43 in addition to CTF-35 and CTF-25 [113][114][115][116][117][118][119][120]. Inhibiting this mode of clearance in primary neurons results in a greater accumulation of cytoplasmic TDP-43 aggregates compared to other cell stressors [113,121,122]. Recently a gain-of-function mutation in CYLD Lysine 63 Deubiquitinase (CYLD) was identified to cause ALS and FTLD [123].…”
Section: Main Textmentioning
confidence: 99%